Pengembangan Ekonomi Wisata Pantai Cemara Paalong Holtekamp, Kota Jayapura dengan Pemanfatan Sumber Daya Lokal: Economic Development of Tourism at Cemara Paalong Beach, Holtekamp, Jayapura City by Utilizing Local Resources - Zulfiana T, Indah Sari; Zebua, Mercyana Trianne; Lado, Meity Luisa Halena; Utomo, Sugito (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Cemara Paloong Beach is one of the beach tourism destinations located in Holtekamp, Muara Tami, Jayapura, Papua. It has natural tourism potential, with a row of pine trees and beautiful beaches, but it still lacks organization to enhance its attractiveness. As a result, this tourist site is less well-known to the broader public than other beach tourist destinations in Jayapura City. The objectives of this community service activity are to enable the partners to create tourism attractions and artificial attractions, such as photo spots, which are popular among visitors at tourist sites, to allow the partners to organize and manage the tourist area to make it more orderly, and to enable the partners to open access through promotion on social media with attractive visual concepts. The use of local wisdom as a concept for tourism economic development aims to enhance the local natural and cultural potential through proper planning and management, thereby making it a source of financial income that will eventually have a positive impact on the economic development of the village community. The methods used include providing training in beach management, such as local wisdom-based arrangements; creating photo spots; financial management; graphic design training for tourism promotion on social media; and hands-on assistance in creating photo spots using on-site recycled materials, such as fallen trees and used tires. The results are that the partners gain knowledge in managing beach tourism, from organization to promotion, and the partners acquire the ability to create attractive, locally based photo spot attractions.